Tracheal mucosal necrosis and sloughing after accidental endotracheal extubation in a child: a case report and literature review - Zhang, Yanting; Zhang, Luobei; Xu, Kang; Chen, Jun; Xu, Ying; Yang, Yihua; Ma, Jing; Liu, Chang (Frontiers in Pediatrics, 2026)
IntroductionAirway obstruction caused by the detachment of obstructing fibrinous tracheal pseudomembrane (OFTP) secondary to airway mucosal injury from endotracheal intubation is extremely rare in clinical practice. Due to the non-specific clinical manifestations and low incidence of this disease, most clinicians tend to overlook it, lack vigilance, and find it difficult to make a definite diagnosis immediately when symptoms appear. After the tracheal mucosa is injured and detached, it can form a valvular obstruction that blocks airway ventilation, leading to obvious dyspnea, acute respiratory distress, and even asphyxia resulting in sudden death of the patient. Early definite diagnosis and correct management are conducive to turning the patient's critical condition around and promoting smooth recovery.Case presentationWe report a case of a pediatric patient who developed acute airway obstruction due to the necrosis and detachment of OFTP after accidental self-extubation of the endotracheal tube following intubation. Before a definite diagnosis was made, non-invasive ventilator-assisted ventilation and nebulization therapy were administered. After the diagnosis was confirmed by flexible bronchoscopy and cervical computed tomography, the necrotic airway mucosal tissue was removed via flexible bronchoscopy. The patient's airway obstruction was successfully relieved, symptoms of inspiratory dyspnea were alleviated, airway patency was restored, and the patient was eventually cured and discharged from the hospital.ConclusionsOFTP caused by accidental endotracheal extubation is a rare clinical condition that leads to acute inspiratory dyspnea. Flexible bronchoscopy is beneficial for diagnosis, as well as for non-invasive and rapid removal of necrotic and detached tracheal mucosal tissue formed by OFTP. This procedure relieves airway obstruction in patients and exerts a positive impact on the diagnosis, treatment, and prognosis of the patients.